Effects of the nutrient inhibition on the yield of DBPFPs by Microcystis aeruginosa - Liu Zhiquan; Huang Rui; Wang Zhu; Cui Fuyi; Hu Chun (IWA Publishing, 2023)
The yield of three disinfection byproduct formation potentials (DBPFPs), including trichloromethane, dichloroacetic acid and trichloroacetic acid formation potential (TCMFP, DCAAFP and TCAAFP), by Microcystis aeruginosa under the nitrate and phosphate inhibition conditions was investigated. The results showed that excessive nitrate could inhibit the growth of M. aeruginosa, but the concentration of DBPFPs in the five fractions of algal metabolites, including hydrophilic extracellular organic matter (EOM), hydrophobic EOM, hydrophilic intracellular organic matter, hydrophobic intracellular organic matter and cell debris, only decreased slightly. Accordingly, the productivity of DBPFPs by M. aeruginosa increased by approximately 40% under the nitrate inhibition condition and the increased productivity of DBPFPs mainly came from EOM. The phosphate inhibition also performed a similar pattern with a lesser extent. The nutrient inhibition did not change the proportion of these three DPBFPs, and TCMFP accounted for approximately 87% of the total DBPFPs. The inhibition could promote M. aeruginosa to secrete more metabolites. However, the cyanobacteria tended to secrete more DBPFPs under the nitrate inhibition condition, which resulted in an increased specific DBPFP, while they tended to secrete more non-DBPFPs under the phosphate inhibition condition, which resulted in a decreased specific DBPFP. HIGHLIGHTS DBPFPs mainly came from a hydrophilic fraction in extracellular organic matter and a hydrophobic fraction in intracellular organic matter.; Nutrient inhibition enhanced the productivity of DBPFP by M. aeruginosa.; Nutrient inhibition promoted M. aeruginosa to secrete more metabolites.; Specific DBPFPs increased with nitrate inhibition and decreased with phosphate inhibition.;